An Attribute of Social Security among Farmers in India - Kaswa, Divya (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
India's economy is heavily dependent on agriculture, both in terms of the employment it creates and its contribution to GDP. A recent economic assessment voiced worry about the declining contribution of capital formation from the agricultural sector to GDP. A research titled "Status Assessment Survey of Farmers" (SAS), which was funded by the Indian government and analysed the situation of farmers for the first time in 2003, revealed the bleak circumstances in which many farmers in India currently find themselves. With an increase in farmer suicide rates in recent years, India has seen a worrisome trend. Newspapers continue to publish daily suicide cases in various sections of the country, reflecting the "crisis in Indian agriculture."